Doxorubicin‐loaded polyphosphate glass microspheres for transarterial chemoembolization. Issue 6 (26th February 2020) - Nix, Hayden P.; Momeni, Arash; Chevrier, Daniel M.; Whitman, Catherine A.; Filiaggi, Mark J.
Abstract: The standard of care for intermediate stage hepatocellular carcinoma is transarterial chemoembolization (TACE). Drug‐eluting bead TACE (DEB‐TACE) has emerged as a leading form of TACE, as it uses highly calibrated microspheres to deliver consistent embolization and controlled drug release to the tumor microenvironment. We report here on doxorubicin (DOX)‐loaded polyphosphate glass microspheres (PGM) as a novel resorbable, radiopaque, preloaded DEB‐TACE platform. Coacervate composed of polyphosphate chains complexed with Ba 2+, Ca 2+, and Cu 2+ can be loaded with DOX prior to PGM synthesis, with PGM production achieved using a water‐in‐oil emulsion technique at room temperature yielding highly spherical particles in clinically relevant size fractions. In vitro, DOX release was found to be linear, pH dependent, and in accordance with Type II non‐Fickian transport. PGM degradation was characterized by an initial burst release of degradation products over 7 days, followed by a plateau in mass loss at approximately 75% over a period of several weeks. in vitro studies indicate that PGM degradation products, namely Cu 2+, are cytotoxic and may interact with eluted DOX to impair its pharmacological activity. With additional compositional considerations, this approach may prove promising for DEB‐TACE applications.